Three-dimensional kinematics of shoulder laxity examination and the relationship to clinical interpretation*. Issue 2 (3rd November 2017) - Staker, Justin L.; Lelwica, Amy E.; Ludewig, Paula M.; Braman, Jonathan P.
Abstract: Understanding clinical test kinematics improves utility of exam techniques. The purposes of this study were as follows: (1) determine inter-examiner repeatability of translation magnitude for the Anterior/Posterior Drawer and Sulcus shoulder laxity tests; (2) describe the relationships between glenohumeral joint translations and subjective grades for each laxity test; and (3) describe the relationship of overall glenohumeral joint laxity to a composite subjective score from the three laxity tests. Eleven subjects with shoulder symptomology were examined with three laxity tests. Motion was tracked with electromagnetic sensors affixed to the humerus and scapula via transcortical pins. ICCs were calculated to determine repeatability of translation magnitudes between two examiners for each test. Descriptive statistics and regression analyses were performed for comparisons of single laxity test grades with translation magnitudes and for composite subjective laxity scores and overall translation across all three tests. Inter-examiner ICCs regarding kinematic repeatability were 0.87 for Anterior Drawer, 0.84 for the Sulcus test, and not calculable for the Posterior Drawer. No linear relationships between subjective grades of individual tests and translation magnitudes were found. The relationship of overall translation with the composite subjective score from all laxity tests was r 2 = 0.75 ( r = 0.86). Clinicians from different disciplines are capable of imparting similar translations during laxity tests. Single-test subjective laxity grades demonstrate large ranges of translation between subjects for the same grade. By combining results of three laxity tests, clinicians are capable of identifying the level of overall shoulder joint laxity in patients.